The Effect of Brand Image and Consumer Attitudes on The Decision to Purchase Batik Jetis Sidoarjo Mediated by Intent to Buy - Muhammad Mufti Mubarok (Universitas Hayam Wuruk Perbanas, 2018)
In the context of regional economic development, the development of the local economy according to its potential is a very important factor. The owners of the batik industry face problems in marketing. In an effort to influence consumer decisions to buy, they must try one of them is to attract consumers. Therefore, they must pay attention to the image and attitude factors of the industrial owners so that consumers also have a positive attitude towards the image of their products. The purpose of this study was to determine the effect of brand image and consumer attitudes on purchasing decisions directly and indirectly mediated by intent to purchase. The population in this study were consumers of Batik Jetis Sidoarjo with a sample of 100 people taken using judgment sampling method. Data collection method uses a questionnaire. Then, the data were analyzed using path analysis with the IBM SPSS 21 program. The results showed thatbrand image has a positive and significant direct effect on purchasing decisions; (2) consumer attitudes also has a significant direct effect on purchasing decisions; (3) Brand image and consumer attitudes have a positive and significant indirect effect on purchasing decisions through intent to purchase. It is advisable for Batik Jetis Sidoarjo innovate their batik products, both from the combination of motivesand colors. They also have to improve the kiosk spatial sector and adequate facilities, and organize batik events and festivals. Increased promotion and marketing see objects classified as new, strategies for batik events to sell and demand and have their own image by visitors.